Globecom '00 - IEEE. Global Telecommunications Conference. Conference Record (Cat. No.00CH37137)
DOI: 10.1109/glocom.2000.891921
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transport of voice over IP over cellular links

Abstract: A bstmct-Internet and cellular technologies are merging t o decrease transport costs and enable IP-based applications t o hundreds of millions of cellular users. Real time voice services will continue t o be dominant in future cellular systems and t o reduce system costs it is desirable t o base all services, including voice, on IP. However, the radio spectrum must be efficiently used t o provide mass-market services a t reasonable prices, but Internet protocol headers are large in size. Moreover, data discard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…With this signalling, the de-compressor asks for a context update from the compressor and during this time interval, all the packets will be discarded. Thus, CRTP does not perform well on error prone links such as wireless links [102] [103].…”
Section: Rtp Header Compressionmentioning
confidence: 99%
“…With this signalling, the de-compressor asks for a context update from the compressor and during this time interval, all the packets will be discarded. Thus, CRTP does not perform well on error prone links such as wireless links [102] [103].…”
Section: Rtp Header Compressionmentioning
confidence: 99%
“…Coupled with transport and link layer protocols capable of partitioning checksum coverage into sensitive and insensitive regions [9], ROCCO was designed to perform well with audio and video codecs which tolerate bit errors in data frames. Studies showed that ROCCO compressed headers to half of the size of those provided by CRTP and remained robust over links with BER rates an order of magnitude higher [10]. In July 2000, Ericsson and Japan Telecom successfully completed a field trial of VoIP over WCDMA using ROCCO [11].…”
Section: A Brief History Of Header Compressionmentioning
confidence: 99%